Netizens’ Reactions to a Transgender Actor’s Pronoun Change in Instagram: An Engagement System Approach - Ayu, Dara Mela; Santi, Vita Nur (PAROLE: Journal of Linguistics and Education, 2023)
This study explores netizens' views on transgender actor Elliot Page's December 2, 2020, Instagram post, in which he changes his pronouns to 'he/they'. This qualitative descriptive study evaluates netizen opinions in Elliot Page's coming-out post on Instagram which garnered over 140.000 reactions at the time of analysis, serves as the context. A selection of 24 comments related to gender pronouns has been chosen for the data. This research seeks to examine how online users express their stances, utilizing the engagement system from appraisal theory and helps categorizing netizens’ comments into monogloss and heterogloss. Based on this analysis, netizens seem to support, oppose, or compromise Elliot's gender pronouns using various types of engagement systems. Supporters tend to use monogloss, opponents use contract heterogloss, and neutrals use expand heterogloss.